Adherence to Recommended Eating Patterns Is Associated With Lower Risk of Peripheral Arterial Disease: Results From the Women's Health Initiative. Issue 2 (August 2021) - Chen, Guo-Chong; Arthur, Rhonda; Mossavar-Rahmani, Yasmin; Xue, Xiaonan; Haring, Bernhard; Shadyab, Aladdin H.; Allison, Matthew A.; Liu, Simin; Tinker, Lesley F.; Saquib, Nazmus; Coday, Mace; Shikany, James M.; et al.
Abstract : The potential role of nutritional factors in the development of peripheral arterial disease (PAD) remains poorly understood. We evaluated multiple recommended eating patterns as reflected by predefined diet quality indices in relation to long-term risk of PAD. We included 138 506 US postmenopausal women in the Women's Health Initiative who had no known PAD at baseline (1993–1998). Four diet quality indices, including alternate Mediterranean diet index, alternate Healthy Eating Index-2010, Dietary Approaches to Stop Hypertension diet index, and Healthy Eating Index-2015, were derived using dietary information collected by a validated food frequency questionnaire at baseline. Incident cases of symptomatic PAD in the lower extremities were ascertained and adjudicated through March 2019 via medical record review. During a median 18.6 years of follow-up, 1036 incident PAD cases were identified. After multivariable adjustment, all diet quality scores were significantly and inversely associated with 21% (for alternate Healthy Eating Index 2010) to 34% (for Dietary Approaches to Stop Hypertension index) lower risk of PAD when comparing the highest with the lowest quartiles (all P -for-trend values ⩽0.010). Among contributing food groups and nutrients, intakes of legumes, dietary fiber, and vegetable protein were associated lower risk of PAD, while intakes of unprocessed red meat, processed meat, and regular soft drinks were associated with higher risk. In a broad sample of US postmenopausal women, adhering to different recommended eating patterns is associated with lower risk of PAD. Our findings suggest that current clinical and public health strategies that recommend healthful eating patterns may also be applicable to PAD prevention. Abstract : Supplemental Digital Content is available in the text.